Bovine Embryo-Secreted microRNA-30c Is a Potential Non-invasive Biomarker for Hampered Preimplantation Developmental Competence - Lin, Xiaoyuan; Beckers, Evy; Mc Cafferty, Séan; Gansemans, Yannick; Joanna Szymańska, Katarzyna; Chaitanya Pavani, Krishna; Catani, João Portela; Van Nieuwerburgh, Filip; Deforce, Dieter; De Sutter, Petra; Van Soom, Ann; Peelman, Luc (Frontiers in Genetics, 2019)
Recently, secreted microRNAs (miRNAs) have received a lot of attention since they may act as autocrine factors. However, how secreted miRNAs influence embryonic development is still poorly understood. We identified 294 miRNAs, 114 known and 180 novel, in the conditioned medium of individually cultured bovine embryos. Of these miRNAs, miR-30c and miR-10b were much more abundant in conditioned medium of slow cleaving embryos compared to intermediate cleaving ones. MiR-10b, miR-novel-44 and miR-novel-45 were higher expressed in the conditioned medium of degenerate embryos compared to blastocysts, while the reverse was observed for miR-novel-113 and miR-novel-139. Supplementation of miR-30c mimics into the culture medium confirmed the uptake of miR-30c mimics by embryos and resulted in increased cell apoptosis, as also shown after delivery of miR-30c mimics in Madin-Darby bovine kidney cells (MDBKs). We also demonstrated that miR-30c directly targets Cyclin-dependent kinase 12 (CDK12) through its 3’ untranslated region (3’-UTR) and inhibits its expression. Overexpression and downregulation of CDK12 revealed the opposite results of the delivery of miRNA-30c mimics and inhibitor. The significant down-regulation of several tested DNA damage response (DDR) genes, after increasing miR-30c or reducing CDK12 expression, suggests a possible role for miR-30c in regulating embryo development through DDR pathways.